Democracy Beyond Hegemony. Issue 2 (1st April 2019) - Purcell, Mark
Abstract : This article asks whether Laclau and Mouffe are the right theoretical partners for thinking about the project of democracy today. It concludes that they still have quite a lot to offer that project, but it also suggests we should be wary of embracing their thought too wholeheartedly, specifically because of their fondness for Gramsci and hegemony, and perhaps also, as a result, their willingness to engage the state and its institutions in the struggle for democracy.